Closing the gap: the maturing of quality assurance in Australian university libraries - Tang, Karen (2012)
A benchmarking review of the quality assurance practices of the libraries of the Australian Technology Network conducted in 2006 revealed exemplars of best practice, but also sector-wide gaps. A follow-up review in 2010 indicated the best practices that remain relevant.While some gaps persist, there has been improvement across the libraries and the development of greater “quality maturity”.